Joint Study on Western Ghats Development Programme in Maharashtra - Planning Commission (Planning Commission, 1993)
The need to conserve natural resources and the environment, particularly to prevent further damage to the fragile and irreplceable eco-system, was recognised by the Government of India, long back. In this back drop the Hill Areas of the country, particularly the Himalayan and the Western Ghats regions, have been recognised as areas in need of special attention 2. The principle of an area approach was accepted by the National Development Council (NDC) in May, 1972 for the accelerated development of the Western Ghats Region, The Western Ghats Region runs into a length of 1600 kms., more or less parallel to the west coast of the peninsula starting from the mouth of river Tapti in Dhule district of Maharashtra and ending up at Kanyakumari, the southern most tip of India in Tamil Nadu.
Design, Instruments, Instructions, Etc. By Directorate of Economics and Statistics (Government of Maharashtra) Bombay and Programme Evaluation Organisation Planning Commission